The puzzle of post-pandemic recovery, transatlantic relations and European solidarity - Czech, Sławomir (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: The coronacrisis has highlighted the fragility of the highly interdependent world economic order. The economic recession following numerous lockdowns weakened the position of the West in the geopolitical arena. Thus economic recovery is a must, though its significance for the US and the EU differs considerably. Aim: The paper aims to discuss the state and prospects of transatlantic relations in the era of new challenges posed in front of the US and the EU. We have selected two main issues: the incremental rivalry between the US and China, and the solidarity principle within the EU. The departure point for the analysis is the assumption that the tightening of economic cooperation between the US and the EU seems desired, but it might also lead to socioeconomic consequences questioning European solidarity in the long term. We employ the perspective of institutionalist political economy to understand the interplay between actors and the rules they create. We assume thus that actors pursue their goals, but must take various limitations into account. We also refer to the literature on economic policymaking and economic systems. Results: Under possible regionalization of the world economy after the COVID-19 pandemic, transatlantic relations will be under pressure to generate growth. As far as the US is willing to embrace this imperative, the EU might face the dilemma between struggling for better economic performance and rebuilding solidarity between member countries.